Continuing professional development: a cross-cultural learning approach. (25th February 2005) - Chen, Jau-Rong; Ju, Teresa L.
The pursuit of a postgraduate degree can be seen as a continuous process in which students develop their professional competence. Literature reveals many conceptual frameworks of knowledge applicable to professional development and education. However, at present, there is little research that explores the forms of individual Continuing Professional Development (CPD) situated in different cultural contexts. In order to examine the issue of CPD in different contexts, this paper critically reviews, evaluates and synthesises theories of cross-cultural adjustment and international students' sojourn activities while engaged in academic pursuit. Empirical evidence, collected from the experience of Taiwanese postgraduate students in the UK, is used to build a grounded theory of cross-cultural adjustment. This study shows that cross-cultural adjustment is a continuous process in which international students develop their competence of instrumental diversity, where there is increased pressure and consequent possibility of contingent behaviour. Furthermore, this study provides a conceptual framework for future research in cross-cultural adjustment within different host countries, serving as a basic framework for helping organisations anticipate and effectively manage the adjustment problems faced by international students and employees.